Cerium oxide capping on Y-doped HfO2 films for ferroelectric phase stabilization with endurance improvement. (3rd February 2022) - Mizutani, Kazuto; Hoshii, Takuya; Wakabayashi, Hitoshi; Tsutsui, Kazuo; Chang, Edward Y.; Kakushima, Kuniyuki
Abstract: The effects of 1 nm thick CeO x capping on 7.5 nm thick Y-doped HfO2 films on the ferroelectric characteristics are investigated. From the ferroelectric characteristics of the samples annealed at different temperatures from 450 °C to 600 °C and annealing durations, the time ( τ ) required to stabilize the ferroelectric phase at each temperature was shortened by the capping. The identical activation energy ( E a ) of 2.65 eV for ferroelectric stabilization without and with capping suggests the same kinetics for phase transformation. However, an increase in the remnant polarization ( P r ) was obtained. Only a few Ce atoms diffused into the underlying HfO2 film even after 600 °C annealing. Ferroelectric switching tests revealed an improvement in endurance from 10 7 to 10 10 by the capping, presumably owing to the suppression of conductive filament formation. Therefore, CeO x capping is effective in promoting the ferroelectric phase in HfO2 with high switching endurance.